Sale leisure activities of children and youth in out of school educational establishments of physical culture and sports destinations - N.V. Tikhonova (Physical Education of Students, 2014)
Purpose : To determine the role of extracurricular educational establishments of physical culture sports direction in providing leisure activities for children and youth. Material : The results of the analysis of the scientific and methodological literature, statistical reports of the Ministry of Youth and Sports of Ukraine, authorities of Physical Culture and Sport, authorities the Department of Education and Science. Results : Based on the analysis of statistical reports determined satisfactory condition and leisure activities in non-school educational establishments physical culture sports direction. This is confirmed by an increase in the number of pupils and students dealing all kinds of physical culture health improvement work. Also, the decline in the number of pupils and students classified for health reasons for the special medical group. Conclusions : Our data showed that extracurricular educational institutions physical culture sports direction have a place in leisure activities. They play an important role in motor activity, substantial leisure and healthy lifestyles for children and young people of our country.